Die Frage der Qualifizierung in einer digitalisierten Gesellschaft - Klaus Kornwachs; Nico Stehr (Wirtschaftsdienst, 2021)
Die Digitalisierung treibt den Wandel der Welt der Arbeit voran. Dieser Wandel könnte durch die wissenschaftlich-technische Dynamik, die von Unternehmen kontrollierte Nachfrage nach qualifizierten Arbeitskräften oder vielmehr durch das Qualifikationsangebot der Arbeitnehmenden determiniert sein. Dabei ist fraglich, welcher kognitiven und sozialen Fertigkeiten es in der Vierten Industriellen Revolution bedarf. – – Although current discussions about the future requirements of occupational qualifications as a result of digitization always emphasise the 'that', they rarely address the concrete content of future knowledge and skills. It is argued that certain technical developments are actually determined by the rising level and increasing availability of qualifications. It suggests that the question of the nature of future qualifications should not only be raised in the context of employment, but also for society as a whole. Examples of the presence of novel but not widely mobilised knowledge and skills are empirically found in start-up companies.
Keywords: I25; J24; M53; 330